Epidural Analgesia for Palliative Pain Management for A Patient with An Advanced Stage Prostate Cancer: A Case Report - Susilo, Astrid Pratidina; Pryambodho, Pryambodho (Indonesian Journal of Cancer, 2024)
Introduction: Patients with advanced-stage cancer should be able to stay at home with their families without suffering from pain. This case report aims to discuss challenges in pain management of a patient with bone metastasis of prostate cancer who received epidural analgesia at home. Challenges were related to the patients, health professionals, and system. Understanding each factor will bring insights to develop a workable pain management program in the palliative setting. Case Presentation: A 66-year-old male was diagnosed with left sacroiliac joint pain due to metastatic prostate cancer. After a three-year history of prostate cancer and ineffective chemotherapy, the patient complained of pain in the left hip that did not improve with conventional medications (paracetamol, tramadol, and Morphine Sustained Release/MST). In response, the consideration of an epidural implant emerged as a potential solution, offering the prospect of home-based care and autonomous medication administration through an epidural continuous block with intermittent drug injection. Conclusions: This case highlights home-based interventional pain management for cancer, addressing challenges at the patient, health professional, and system level. Overcoming these challenges requires a multidisciplinary approach and robust institutional policies. The insights gained offer valuable lessons for hospitals aiming to enhance the competence of pain and palliative care teams and establish comprehensive support systems in hospital and home settings.